Comparing Robotic Lung Resection with Thoracotomy and Video-Assisted Thoracoscopic Surgery Cases Entered into the Society of Thoracic Surgeons Database. Issue 1 (January 2014) - Farivar, Alexander S.; Cerfolio, Robert J.; Vallières, Eric; Knight, Ariel W.; Bryant, Ayesha; Lingala, Vijaya; Aye, Ralph W.; Louie, Brian E.
Objective: The use of robotic lung surgery has increased dramatically despite being a new, costly technology with undefined benefits over standard of care. There is a paucity of published comparative articles justifying its use or cost. Furthermore, outcomes regarding robotic lung resection are either from single institutions with in-house historical comparisons or based on limited numbers. We compared consecutive robotic anatomic lung resections performed at two institutions with matched data from The Society of Thoracic Surgeons (STS) National Database for all open and video-assisted thoracoscopic surgery (VATS) resections. We sought to define any benefits to a robotic approach versus national outcomes after thoracotomy and VATS. Methods: Data from all consecutive robotic anatomic lung resections were collected from two institutions (n = 181) from January 2010 until January 2012 and matched against the same variables for anatomic resections via thoracotomy (n = 5913) and VATS (n = 4612) from the STS National Database. Patients with clinical N2, N3, and M1 disease were excluded. Results: There was a significant decrease in 30-day mortality and postoperative blood transfusion after robotic lung resection relative to VATS and thoracotomy. The patients stayed in the hospital 2 days less after robotic surgery than VATS and 4 days less than after thoracotomy. Robotic surgery led to fewer air leaks, intraoperative blood transfusions, need for perioperative bronchoscopy or reintubation, pneumonias, and atrial arrhythmias compared with thoracotomy. Conclusions: This is the first comparative analysis using national STS data. It suggests potential benefits of robotic surgery relative to VATS and thoracotomy, particularly in reducing length of stay, 30-day mortality, and postoperative blood transfusion.